Pengaruh Return on Asset, Net Profit Margin, Earning per Share, Debt to Equity Ratio, dan Total Assets Turn Over terhadap Dividend Payout Ratio pada Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2012-2015 - Indrayani, Puput; Wibisono, Haris; Purbandari, Theresia (JRMA | Jurnal Riset Manajemen dan Akuntansi, 2020)
This study aims to prove empirically the effect of return on assets, net profit margin, earnings per share, debt to equity ratio, and total assets turnover over dividend payout ratio in manufacturing companies listed in Indonesia Stock Exchange period 2012-2015. The sample used in this study is a manufacturing company listed on the Indonesia Stock Exchange in 2012-2015. The total sample of 136 companies is determined based on purposive sampling method. This research used multiple linear regression method with SPSS version 17 program. The results of this study are not able to prove that the return on assets, net profit margin, earnings per share, debt to equity ratio, and total assets turn over affect the dividend payout ratio.